Targeted Killing of Ismail Haniyeh: International Law Perspective - Muhammad Fathi; Muhammad Alfin Imanullah; Aisyah Ajeng Putri Riyanto; Sayyid Nabil Mahakim Najwa (Lampung Journal of International Law, 2026)
The unresolved Palestine-Israel conflict has intensified debate over the legality and ethical implications of targeted killings under international law. This normative legal study examines the killing of Ismail Haniyeh in Tehran by analyzing its compatibility with the principles of distinction, proportionality, and necessity under international humanitarian law. The operation also raises serious concerns under Article 6 of the ICCPR, which prohibits arbitrary deprivation of life, and Article 14, which guarantees fair trial and due process protections. In addition, the operation potentially violated Iran’s sovereignty and territorial integrity under Article 2(4) of the United Nations Charter, which prohibits the use of force against another state. The study highlights the need for stronger accountability mechanisms, greater judicial oversight, and the prioritization of non-lethal alternatives in counterterrorism operations. It further emphasizes that adherence to international legal norms and efforts to address the root causes of the Palestine-Israel conflict remain essential for protecting human rights and maintaining international legal order..